Antidepressant and anti-inflammatory effects of a combined fluoxetine and celecoxib treatment in a rat model of depression - Trongtorsak, Petcharat; Olankijanunt, Wanida; Trongtorsak, Angkawipa; Intamaso, Uraiwan (Chulalongkorn Medical Journal, 2023)
Background : An evidence suggests a potential therapeutic target of depression toward treating inflammation with nonsteroidal anti-inflammatory drugs (NSAIDs). However, the efficacy of the combined standard antidepressant with NSAID treatment still remains uncertain. Objective : To examine the effects of fluoxetine (serotonin reuptake inhibitor) in adjunct with celecoxib (specific COX-2 inhibitor) on depression-like behavior and inflammation in rats with chronic mild stress (CMS) induced depression. Methods : The rats were divided into 4 groups: control, CMS, CMS with fluoxetine treatment (5 mg/kg/d), and CMS with fluoxetine and celecoxib treatment (5 mg/kg/d each). All treatments were continued for 5 weeks. The depression-like behavior was examined using forced swimming test. Blood samples were collected for biochemical analysis of plasma levels of cortisol, prostaglandin E2 (PGE2), interleukin-1 (IL-1 ), tumor necrosis factor- (TNF- , C-reactive protein (CRP), and an oxidative stress marker malondialdehyde (MDA). Results : The combined treatment decreased depression-like behavior to the same extent as fluoxetine treatment alone. However, the adjunctive celecoxib significantly reversed the effect of fluoxetine in lowering the plasma cortisol level which implied the aggravation of hypothalamicpituitary- adrenal axis (HPA axis) dysregulation, and also increased body weight gain compared with fluoxetine, suggesting a possibility of body fluid retention. Both drug treatments showed a comparable degree in lowering the plasma levels of PGE2, TNF- , CRP and MDA. Nonetheless, fluoxetine showed no significant effect on plasma IL-1 level; whereas the adjunctive celecoxib treatment lowered this proinflammatory cytokine to almost normal. Conclusion : The results suggest that the combined celecoxib treatment shows no synergistic antidepressant effect to fluoxetine, but may exacerbate the HPA axis hyperactivation.